The impact of intensive correction orders on re-offending - Clare Ringland
This study examined the risk of re-offending of those who received an intensive correction order, relative to those who received periodic detention and suspended sentences with supervision. Method: Details of offenders’ demographic and offence characteristics, prior convictions and penalties received, and re-offences were extracted from the Re-offending Database maintained by the NSW Bureau of Crime Statistics and Research. Using propensity score modelling, offenders who received an ICO as a principal penalty in a NSW court between 1 October 2010 and 30 September 2012 were matched to two comparable groups of offenders who received periodic detention between 1 October 2007 and 30 September 2009 and suspended sentences with supervision between 1 October 2010 and 30 September 2012. A supplementary comparison with those who received suspended sentences with supervision included matching on Level of Service Inventory - Revised (LSI-R) assessment scores, in addition to demographic and offending characteristics. Time to first re-offence was estimated using the Nelson-Aalen estimator of the cumulative hazard rate function and compared between groups using Cox proportional hazards regression. Results: An offender on an ICO had 33 per cent less risk of re-offending than an offender on periodic detention (HR=0.67, 95% confidence interval (0.55, 0.83), p<.001). There was no significant difference in re-offending between those who received ICOs and supervised suspended sentences after taking into account LSI-R assessment scores. Conclusion: There is some evidence to suggest that ICOs are more effective than periodic detention in terms of re-offending rates. However, future evaluations should include more detailed offender, treatment and program participation information in order to better understand any observed differences between comparison groups